Acceptance of Family Planning Amongst Patients Attending Dhulikhel Hospital Obstetrics and Gynecology Department - Shrestha, A; Kayastha, B; Manandhar, S; Chawla, CD (Kathmandu University Medical Journal, 2015)
Background Knowledge of contraceptive methods is an important factor for an individual to use or not use of family planning methods. In Nepal, at least one modern method of family planning is universal amongst both men and women. Objectives To assess the knowledge, attitude regarding various family planning methods and practice of contraceptives amongst couples attending Dhulikhel Hospital Obstetrics and Gynecology Department. Methods Five hundred and fifteen couples were interviewed. Their knowledge, attitude and practice of contraception were evaluated with the help of pre-evaluated questionnaire. The other variable used were the age of the couple, parity, educational status and economic status having effect on the contraceptive acceptance were taken into consideration. Descriptive analysis was conducted to obtain percentages. Results We observed that 74.98% of women were in the age group of 20-29 years and 59.22% of men were within the age group of 20-29 years. Teen age mothers were 17.86% and teen age fathers were 1.35%. In our study, we observed that higher the educational level better was the acceptance for family planning methods. The higher income group had less number of children compared to lesser income group. In our study, we noticed that all the couples knew about different methods of family planning, main sources of information were television, pamphlets and healthworkers. Only 16 males had undergone vasectomy and 32 women had undergone tubectomy. Fewer number of vasectomy was due to the belief that undergoing vasectomy will make the male partner weak physically. 13.20% of women preferred Depot medroxy progesterone as a temporary method of family planning, 13% of males preferred condom as a temporary method of family planning. Conclusion We conclude that education plays a vital role in the acceptance of family planning. As couples who have higher education level tend to have higher income and they have lesser number of children. They are more receptive towards counseling and agree upon the various methods of family planning. The easy accessibility to the various media like radio, television tend to make people aware of various methods of family planning. Kathmandu University Medical Journal Vol.12(3) 2014; 198-201